Designing a case study protocol for application in IS research - Pervan, Graham; Maimbo, M. (PACIS, 2005)
A review of the literature has shown that there is a growing call for the use of the case research method in IS research. However, it has been noted that there are few guidelines on how to conduct case research in the field of IS, particularly with respect to the development of Case Study Protocols. This article therefore endeavours to overcome this shortcoming by presenting a set of guidelines that may be used by in the development of such protocols. In essence, a Case Study Protocol (CSP) is a set of comprehensive guidelines that is an integral part of the case research design and contains the procedures for conducting the research, the research instrument itself, and the guidelines for data analysis. By developing a CSP, researchers are forced to consider all issues relevant to their research and this in turn contributes to more rigorous (case) research that has greater internal and external validity.